2007
DOI: 10.1016/j.pharmthera.2006.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of intracellular signaling in insulin-mediated regulation of drug metabolizing enzyme gene and protein expression

Abstract: Endogenous factors, including hormones, growth factors and cytokines, play an important role in the regulation of hepatic drug metabolizing enzyme expression in both physiological and pathophysiological conditions. Alterations of hepatic drug metabolizing enzymes gene and protein expression, observed in diabetes, fasting, obesity, protein-calorie malnutrition and long-term alcohol consumption alters the metabolism of xenobiotics, including procarcinogens, carcinogens, toxicants, and therapeutic agents and may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(67 citation statements)
references
References 278 publications
(299 reference statements)
6
59
0
2
Order By: Relevance
“…We also found 5 that fructose-fed female rats displayed a significantly reduced expression of liver insulin-related substrate-2 (IRS-2) [17], one of the key insulin-signaling proteins in the liver [25].…”
Section: Introductionmentioning
confidence: 79%
“…We also found 5 that fructose-fed female rats displayed a significantly reduced expression of liver insulin-related substrate-2 (IRS-2) [17], one of the key insulin-signaling proteins in the liver [25].…”
Section: Introductionmentioning
confidence: 79%
“…A variety of environmental carcinogens, including low levels of UV-B irradiation, also activate Nrf2 and up-regulate AREresponsive gene products to enhance protection against cellular and molecular damage that can induce cancer (17). In addition, changes in insulin levels during fasting induce a mild oxidative stress and an alteration of the expression of Nrf2-induced enzymes (18).…”
mentioning
confidence: 99%
“…It was also shown that the insulin-mediated increase in GST A protein levels in hepatocytes is independent of MEK1 inhibition that lead to ERK1/2 pathway blockage, in addition to p38 MAPK, HSP27 and PKC inhibition in hepatocytes (Kim et al, 2006). Consequently, PI3K/Akt/p70S6K signaling was determined functioning in the insulin-mediated upregulation of the antioxidant defense system, and potentially enhances the hepatocytes susceptibility to xenobiotic-or oxidative stressmediated damage (Kim and Novak, 2007).…”
Section: Interaction Of Gst With Proteins In Signal Transduction Pathmentioning
confidence: 99%